Price elasticity of demand for psychiatric consultation in a Nigerian psychiatric service (2016)
Objective: This paper addresses price elasticity of demand (PED) in a region where most patients make payments for consultations out of pocket. PED is a measure of the responsiveness of the quantity demanded of goods or services to changes in price. The study was done in the context of an outpatient psychiatric clinic in a sub –Saharan African country. Methods: The study was performed at the University College Hospital (UCH), Ibadan, Nigeria. Aggregate data were collected ed on weekly clinic attendance over a 24- month period October 2008 - September 2010 representing 12 months before, to 12months after a 67% increase in price of outpatient psychiatric consultation. The average weekly clinic attendance prior to the increase was compared to the average clinic attendance after the price increase. Arc-PED for consultation was also estimated. Results: Clinic attendance dropped immediately and significantly in the weeks following the price increase. There was a 34.4% reduction in average weekly clinic attendance. Arc-PED for psychiatric consultation was -0.85. Conclusion: In comparison to reported PED on health care goods and services, this study finds a relatively high PED in psychiatric consultation following an increase in price of user fees of psychiatric consultation.